Analysis of Textbook “Ilmu Saraf Untuk Pemula” Third Edition Writen by Abu Razin and Ummu Razin (Development Textbook Principles) - Afdhal Fikri Mirma; Talqis Nurdianto; Zainal Abidin Hajib (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2023)
This article aimed to analyze the book "Sarf science for beginners third edition by Abu Razin and Ummu Razin" based on the theory of development textbook principles and to find out the strengths and weaknesses of textbook. This research was qualitative method, it is literature research with descriptive analysis method. According to the results of this research, the Sharaf Science book for beginners has been revised and developed twice, based on suggestions and recommendations from teachers and students. The sociocultural principle is a weakness in this textbook because the author paid little attention to this principle, especially in giving examples in the discussion of sarf which aims to understand the Qur'an. Supposedly, giving examples in this book should also represent the themes of Arab culture. There is no appropriate use for this book for learners who is younger than 15 years old since it doesn't address the psychological state of these learners. The principles of psychology, pedagogy, and language are the strengths of this book. There are several striking strengths of this book, including how the author facilitates the ability of students to learn independently, and how teachers are given several videos for free about the explanation and teaching of the book, directly practiced by the author. This textbook still has few typos and a lot of blank spaces on some pages, and it does not explain in detail, for example in the discussion of fi'il mu'tal, the origin of the word and the history of its changes, although the author has provided a video of the learning process on YouTube. How good it would be if the explanation was later included in the book.